Association of residence and regional location with depression prevalence in Indonesia: an analysis of the Indonesian health survey 2023 - Rahayu, Fima Perdani; Alvian, Sofa Dewi; Abdulah, Rizky (Universitas Ahmad Dahlan, 2025)
Depression is a mental health condition characterized by persistent sadness, loss of interest in daily activities, and fatigue. It affects an individual’s ability to function and engage in everyday life. In Indonesia, depression is a growing public health concern. Geographic factors, such as residence (urban vs rural) and regional (West, Central, East Indonesia), may influence the prevalence of depression due to variations in social environment, healthcare access, and stress exposure. This study aims to identify factors associated with depression based on residential and regional location, utilizing secondary data from the 2023 Indonesian Health Survey (SKI) with a descriptive research design and cross-sectional method. This study employed a descriptive, cross-sectional design using data from the 2023 Indonesian Health Survey (SKI). The inclusion criteria were individuals aged 18 and above who self-reported depression. Key variables analyzed included gender, age, residence (urban or rural), and regional location in Indonesia. A Chi-square test was applied to examine the association between depression and geographic factors, with a significance level of p < 0.05. A total of 10,504 subjects with self-reported depression were identified, of which 67.76% were female. The analysis showed a higher depression prevalence among urban residents, 60.78% compared to rural areas, 32.23%. Additionally, depression prevalence was higher in Western Indonesia (60.22%) than in Central and Eastern Indonesia. The analysis revealed a significant association between residence, regional area, and depression in Indonesia, with p-values of 0.001 for all three. Therefore, this study concludes that there is a significant association between self-reported depression, residential and regional location, with urban dwellers exhibiting a higher prevalence of depression (p<0.005). These findings highlight the need for enhanced mental health services in urban areas to address the higher depression rates.